Evaluasi Implementasi Keselamatan dan Kesehatan Kerja (K3) di Laboratorium Jalan Raya Universitas Lampung - Kadek Adi Mahendra (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Occupational Safety and Health (OSH) is a fundamental aspect in creating a safe working environment, especially in high-risk laboratories such as road laboratories. Although the use of this laboratory is quite intensive for practical activities and research at the University of Lampung, to date there has been no comprehensive study on the extent to which OSH is effectively implemented. Therefore, this study aims to evaluate the implementation of OSH in the Road Laboratory of the University of Lampung with reference to national regulations. This study uses a qualitative descriptive approach with the location at the Road Laboratory of the Faculty of Engineering, University of Lampung. The research population includes students, lecturers, and laboratory staff, while the sample is determined purposively. Data collection techniques were carried out through observation, semi-structured interviews, questionnaires, and analysis of SOP documents and safety reports. The data were analyzed descriptively through categorization, interpretation, and comparison with Permenaker No. 5 of 2018 and ISO 45001:2018. The results of the study indicate that although most OSH facilities, such as PPE and SOPs, are available, the level of user compliance still varies and waste management is not yet optimal. The conclusion of this study is that there is a need to increase socialization, supervision, and strengthen the OSH management system so that laboratories can function safely, effectively, and efficiently.